2016
DOI: 10.1039/c6ra17194j
|View full text |Cite
|
Sign up to set email alerts
|

Self-supported tungsten/tungsten dioxide nanowires array as an efficient electrocatalyst in the hydrogen evolution reaction

Abstract: A tungsten/tungsten dioxide nanowires array was constructed on a carbon paper through the thermal annealing of tungsten trioxide, and was proven to be an efficient hydrogen evolution cathode with strong durability in acidic solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Electrochemical impedance spectroscopic (EIS) measurements were performed to determine charge-transfer resistance ( R ct ) during the hydrogen evolution reaction. R ct largely corresponds to the HER kinetics at the electrode–electrolyte interface at low frequencies. , The Nyquist plots of the as-synthesized and the annealed samples are presented in Figures S10a and S10b, respectively. The plots exhibited two semicircles and were fit with a two-time constant model, and the equivalent circuit diagram is depicted in Figure S10c.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopic (EIS) measurements were performed to determine charge-transfer resistance ( R ct ) during the hydrogen evolution reaction. R ct largely corresponds to the HER kinetics at the electrode–electrolyte interface at low frequencies. , The Nyquist plots of the as-synthesized and the annealed samples are presented in Figures S10a and S10b, respectively. The plots exhibited two semicircles and were fit with a two-time constant model, and the equivalent circuit diagram is depicted in Figure S10c.…”
Section: Resultsmentioning
confidence: 99%
“…Through synergistic effect of components, the multi‐component catalysts are fabricated to overcome the instability of active components in the acid and alkaline electrolyte. For example, the tungsten/tungsten dioxide nanowires array on carbon paper (W/WO 2 NA@CP) provides an enhanced catalytic activity due to the fast electron transport from the carbon paper to W/WO 2 nanowires [121] . Through electrospinning method, the SiO 2 /WO 3 catalyst is endowed with enhanced interaction between SiO 2 and WO 3 , displaying 6.6 times HER activity than the bulk catalyst [122] .…”
Section: Design Principles For Tungsten Oxidementioning
confidence: 99%
“…For example, the tungsten/tungsten dioxide nanowires array on carbon paper (W/WO 2 NA@CP) provides an enhanced catalytic activity due to the fast electron transport from the carbon paper to W/ WO 2 nanowires. [121] Through electrospinning method, the SiO 2 / WO 3 catalyst is endowed with enhanced interaction between SiO 2 and WO 3 , displaying 6.6 times HER activity than the bulk catalyst. [122] Moreover, a unique string-like structure of NiWO 4 -WO 3 -WO 2.9 composite was developed, in which WO 2.9 plays a critical role in the electrocatalytic activity for HER.…”
Section: Multicomponent Catalysismentioning
confidence: 99%
“…26 Zhang et al demonstrated that W/WO 2 NA@CP requires 297 mV hydrogen evolution over-potential to drive the current density of 10 mA cm −2 . 27 Xiao's group showed through theoretical simulations and experimental results that the incorporation of transition metal atoms including Fe, Co, Ni, and Cu can weaken the H interaction on M-W sites, consequently accelerating the HER process. 28 Inspired by this, we prepared self-supporting Ni-doped WO x for HER without additional dopant.…”
mentioning
confidence: 99%